Implementation of the K-Means Clustering for Teacher Performance Assessment Grouping (PKG) at MI Bani Hasyim Cerme - Bagus Firmansyah; Umi Chotijah (Jurnal Riset Informatika, 2022)
Evaluation of teacher performance at MI Bani Hasyim Cerme still uses the manual method. Using office applications such as excel and word results in a significant accumulation of data that makes it difficult for school principals to calculate scores and evaluate the results of clustering or teacher performance scores, so it is wasteful of energy, time, and cost. The k-Means clustering method is expected to facilitate the clustering process of teacher performance values ​​as a source of information and make it easy for school principals to classify teacher performance results. This research aims to obtain clustering values ​​on teacher performance assessment data and to replace the teacher performance assessment system at MI Bani Hasyim, which was previously carried out conventionally into a web-based system. The results of this study are the clustering values ​​of teacher performance assessment and a web-based teacher performance appraisal system. It is expected to facilitate the process of evaluating teacher performance in the Bani Hasyim primary school in the future.